2017
DOI: 10.1371/journal.pone.0174419
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study: Mothers of late preterm infants relate their experiences of community-based care

Abstract: PurposeIn Alberta, the high occurrence of late preterm infants and early hospital discharge of mother-infant dyads has implications for postpartum care in the community. Shortened hospital stay and complexities surrounding the care of biologically and developmentally immature late preterm infants heighten anxiety and fears. Our descriptive phenomenological study explores mothers’ experience of caring for their late preterm infants in the community.MethodsEleven mothers were interviewed using a semi-structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
12

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 29 publications
(32 reference statements)
1
28
0
12
Order By: Relevance
“…This article will focus on breastfeeding practices. Other results of our study can be found elsewhere [23]. Mothers completed a questionnaire about maternal characteristics at delivery, infant characteristics, and demographic information.…”
Section: Methodsmentioning
confidence: 99%
“…This article will focus on breastfeeding practices. Other results of our study can be found elsewhere [23]. Mothers completed a questionnaire about maternal characteristics at delivery, infant characteristics, and demographic information.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the nature of the Delphi technique, that comments are used to build consensus, study participants were informed that if they chose to withdraw from the study, data cannot be removed. We employed a "real-time" Delphi, in which multiple rounds were compressed to occur over several meetings [24]. We used three rounds of questioning.…”
Section: Significance To Feeding How Phns Can Respondmentioning
confidence: 99%
“…Each round provided an opportunity for the experts to respond to and revise their answer in light of other group members' previous responses. Over multiple rounds, the process gradually led to consensus or near-consensus [24]. After the Delphi rounds AD ensured all current literature was included until saturation was reached and critically synthesized the information according to systems and important concepts.…”
Section: Significance To Feeding How Phns Can Respondmentioning
confidence: 99%
See 1 more Smart Citation
“…Um atendimento pré-natal qualificado faz-se necessário para que as gestantes de risco sejam identificadas, minimizando possíveis complicações 10 . A relevante concentração de nascimentos prematuros na faixa de idade gestacional entre 34 semanas e 36 semanas e 6 dias, os denominados prematuros tardios 8,19 , configura-se como uma problemática tanto em relação a maior morbidade, como também ao fato de que frequentemente esses bebês recebem cuidados de saúde usuais 20 . Embora equivocadamente sejam percebidos como um grupo com baixo risco para intercorrências, os prematuros tardios representam índices significativos de morbimortalidade quando comparados ao dos nascimentos à termo 21,22 .…”
unclassified